The effects of microgravity exposure on maximal oxygen consumption in humans - Ferretti, Guido (Revista Cubana de Investigaciones Biomédicas, 2019)
After a short summary of the multifactorial models of maximal O2 consumption (VO2max) limitation, microgravity exposure is discussed as a convenient experimental condition to test these models. The following points are highlighted: 1) The decrease of (VO2max) in microgravity concerns specifically exercise performed in upright posture upon resumption of gravity exposure; 2) The decrease of (VO2max) after microgravity exposure has two components: one is fast and is related to cardiovascular adaptation, the other is slow and is related to the development of muscle atrophy; 3) (VO2max) does not decrease during microgravity or in supine posture upon resumption of gravity exposure, if the time in microgravity is sufficiently short; 4) cardiovascular oxygen transport accounts for 70% of (VO2max) limitation also after microgravity exposure.